Dissipative Kerr Solitons: Dissipative Kerr Solitons in a III‐V Microresonator (Laser Photonics Rev. 14(8)/2020). Issue 8 (13th August 2020) - Moille, Gregory; Chang, Lin; Xie, Weiqiang; Rao, Ashutosh; Lu, Xiyuan; Davanço, Marcelo; Bowers, John E.; Srinivasan, Kartik
Abstract : In article number 2000022, Gregory Moille, Lin Chang, Weiqiang Xie, and co‐workers use cryogenic operation to suppress thermo‐refractive effects and realize stable access to dissipative Kerr soliton frequency combs in AlGaAs‐on‐insulator ring resonators. This platform is distinguished by its ultra‐high nonlinearity and potential for low power operation.